The universe - "Maynard, Christopher" (Kingfisher, London, 1994)
Focusing on astronomy, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book studies the solar system and the galaxies beyond, and discusses how and why scientists investigate space, and what the universe may hold for man in the future.